2017
DOI: 10.1080/09297049.2017.1359525
|View full text |Cite
|
Sign up to set email alerts
|

Greater delay discounting among girls, but not boys, with ADHD correlates with cognitive control

Abstract: Cognitive neuroscience models suggest both reward valuation and cognitive control contribute to reward-based decision-making. The current study examined the relationship between cognitive control and delay discounting (i.e., choosing smaller, immediate over larger, delayed rewards) in a large sample of boys and girls diagnosed with attention-deficit/hyperactivity disorder (ADHD; N = 95) and typically developing control children (TD; N = 59). Specifically, we examined performance on multiple measures of cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 59 publications
5
14
1
Order By: Relevance
“…However, PD-ICD patients in these studies had either lower IQ or working memory deficits or were more depressed than non-impulsive patients. All of these factors were previously associated with greater discounting (83)(84)(85)(86). Consistently with our findings, another study (28) reported similar delay discounting comparing PD-ICD and HC.…”
Section: Discussionsupporting
confidence: 92%
“…However, PD-ICD patients in these studies had either lower IQ or working memory deficits or were more depressed than non-impulsive patients. All of these factors were previously associated with greater discounting (83)(84)(85)(86). Consistently with our findings, another study (28) reported similar delay discounting comparing PD-ICD and HC.…”
Section: Discussionsupporting
confidence: 92%
“…Food go/no-go. Guidelines for exclusions as described in Patros et al [37] were followed. No participants needed to be excluded due to the proportion of go trials with RTs <200 ms exceeding .30, or omission error rate exceeding .50 (n = 0), indicating adequate attention during task presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous behavioral studies have reported that children with ADHD have cognitive and motivational deficits (13,14), both of which independently contribute to ADHD symptoms (15)(16)(17). However, it is still under debate whether the cognitive and motivational deficits are independent from (18,19) or associated with each other (20,21). Recent studies seem to suggest a functional overlap between these two pathways, for example, WM training could also improve DD (22,23).…”
Section: Introductionmentioning
confidence: 99%